Question and Answers Forum

All Questions      Topic List

Probability and Statistics Questions

Previous in All Question      Next in All Question      

Previous in Probability and Statistics      Next in Probability and Statistics      

Question Number 76588 by Rio Michael last updated on 28/Dec/19

Given three events A,B, and C sucb that  P(A) = P(C) , P(A ∩ C) = (1/(10)) , P(A ∪ C)=(1/2)  P(C∣B) = (2/7)  , P(B∪C) = (4/5) find   a) P(A)  b) P(B)

$$\mathrm{Given}\:\mathrm{three}\:\mathrm{events}\:\mathrm{A},\mathrm{B},\:\mathrm{and}\:\mathrm{C}\:\mathrm{sucb}\:\mathrm{that} \\ $$$$\mathrm{P}\left(\mathrm{A}\right)\:=\:\mathrm{P}\left(\mathrm{C}\right)\:,\:\mathrm{P}\left(\mathrm{A}\:\cap\:\mathrm{C}\right)\:=\:\frac{\mathrm{1}}{\mathrm{10}}\:,\:\mathrm{P}\left(\mathrm{A}\:\cup\:\mathrm{C}\right)=\frac{\mathrm{1}}{\mathrm{2}} \\ $$$$\mathrm{P}\left(\mathrm{C}\mid\mathrm{B}\right)\:=\:\frac{\mathrm{2}}{\mathrm{7}}\:\:,\:\mathrm{P}\left(\mathrm{B}\cup\mathrm{C}\right)\:=\:\frac{\mathrm{4}}{\mathrm{5}}\:\mathrm{find}\: \\ $$$$\left.\mathrm{a}\right)\:\mathrm{P}\left(\mathrm{A}\right) \\ $$$$\left.\mathrm{b}\right)\:\mathrm{P}\left(\mathrm{B}\right) \\ $$

Answered by john santu last updated on 28/Dec/19

a) consider P(A∪C)= P(A)+P(C)−P(A∩C)  (1/2)=2P(A)−(1/(10))→ P(A) =(3/(10))

$$\left.{a}\right)\:{consider}\:{P}\left({A}\cup{C}\right)=\:{P}\left({A}\right)+{P}\left({C}\right)−{P}\left({A}\cap{C}\right) \\ $$$$\frac{\mathrm{1}}{\mathrm{2}}=\mathrm{2}{P}\left({A}\right)−\frac{\mathrm{1}}{\mathrm{10}}\rightarrow\:{P}\left({A}\right)\:=\frac{\mathrm{3}}{\mathrm{10}} \\ $$

Answered by john santu last updated on 28/Dec/19

b)P(B∪C)=P(B)+P(C)−P(B/C)×P(B)  (4/5)=P(B)+(3/(10))−(2/7)×P(B)  P(B)=((8/(10))−(3/(10)))×(7/5)=(7/(10))

$$\left.{b}\right){P}\left({B}\cup{C}\right)={P}\left({B}\right)+{P}\left({C}\right)−{P}\left({B}/{C}\right)×{P}\left({B}\right) \\ $$$$\frac{\mathrm{4}}{\mathrm{5}}={P}\left({B}\right)+\frac{\mathrm{3}}{\mathrm{10}}−\frac{\mathrm{2}}{\mathrm{7}}×{P}\left({B}\right) \\ $$$${P}\left({B}\right)=\left(\frac{\mathrm{8}}{\mathrm{10}}−\frac{\mathrm{3}}{\mathrm{10}}\right)×\frac{\mathrm{7}}{\mathrm{5}}=\frac{\mathrm{7}}{\mathrm{10}} \\ $$

Commented by Rio Michael last updated on 28/Dec/19

thanks

$$\mathrm{thanks} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com